Cymatium muricinum and other ranellid gastropods major predators of cultured tridacnid clams - Govan, Hugh (Metro Manila, Philippines ICLARM, 1995)
ICLARM Tech. Rep. 49
Keywords: Reproduction; Feeding behaviour; Clam culture; Predation; Recruitment; Environmental factors; Predators